Financial Risk Management: Fixed Income and Foreign Exchange. - Schneeweis, Thomas; Campbell, Tim S.; Kracaw, William A. (Journal of Finance, 1995)
Financial risk management : fixed income and foreign exchange , Financial risk management : fixed income and foreign exchange , کتابخانه دیجیتال و فن آوری اطلاعات دانشگاه امام صادق(ع)